2018
DOI: 10.1111/jdv.15258
|View full text |Cite
|
Sign up to set email alerts
|

Certolizumab pegol for the treatment of patients with moderate‐to‐severe chronic plaque psoriasis: pooled analysis of week 16 data from three randomized controlled trials

Abstract: Background Certolizumab pegol, an Fc‐free, PEG ylated, anti‐tumour necrosis factor ( TNF ) biologic, has demonstrated favourable results in three ongoing, phase 3, randomized, double‐blinded, placebo‐controlled trials in adults with psoriasis. Objective Data were pooled from the ongoing trials to investigate efficacy in selected subgroups and add precision to estimates of treatment effects during the initial 16 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…The strengths of this study are the systematic evaluation of clinical factors associated with advanced fibrosis in a population with severe psoriasis that has been accurately phenotyped. Demographics in our cohort are comparable with those of a reference population (BSTOP study; N = 3722) but also with phase 3 trial populations in North America and Europe, 16 supporting the generalizability of our findings. This study had low levels of missing data.…”
Section: Strengths and Limitationssupporting
confidence: 83%
See 1 more Smart Citation
“…The strengths of this study are the systematic evaluation of clinical factors associated with advanced fibrosis in a population with severe psoriasis that has been accurately phenotyped. Demographics in our cohort are comparable with those of a reference population (BSTOP study; N = 3722) but also with phase 3 trial populations in North America and Europe, 16 supporting the generalizability of our findings. This study had low levels of missing data.…”
Section: Strengths and Limitationssupporting
confidence: 83%
“…We suggest that clinicians managing patients with severe psoriasis, cognizant of psoriasisassociated complications, engage with their management to improve outcomes for patients. Waist circumference, mean (SD), cm 99.5 (15) 101 (16) .09…”
Section: Resultsmentioning
confidence: 99%
“…Three phase 3 trials, conducted in North America and Europe, have evaluated CZP in moderate to severe PSO over the long-term (CIMPASI-1 [NCT02326298], CIMPASI-2 [NCT02326272], and CIMPACT [NCT02346240]). In these 3-year trials, with a combined total of 1020 randomized patients, CZP has demonstrated favorable efficacy, and a safety profile consistent with the anti-TNF class, with data currently reported through 48 weeks [ 26 28 ]. Here, we report efficacy and safety results from the initial 16 weeks of a 52-week phase 2/3 trial of CZP in Japanese patients with moderate to severe PSO (NCT03051217); this study is the first to evaluate CZP for the treatment of psoriasis in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…15 In a pooled analysis of these three phase III trials (CIMPASI-1, CIMPASI-2 and CIM-PACT), which included 850 patients who received treatment with certolizumab or placebo, both doses of certolizumab gave statistically significant and clinically meaningful improvements in PASI75 and PGA responder rates compared with placebo after 16 weeks' treatment (75-80% vs. 8% and 55-64% vs. 3%, respectively; all P < 0.0001). 24 The rapid and sustained efficacy of certolizumab in our patient cohort can reassure clinicians that many of their patients are likely to experience improvements with 'real-world' use of the drug at a rheumatologic dose (i.e. 400 mg every 2 weeks for the first 4 weeks and 200 mg every 2 weeks thereafter) and that its efficacy is not limited to the dosage regimens used in the clinical trials mentioned above.…”
Section: Discussionmentioning
confidence: 88%